Architecture and Protocols for Robust NGN - Tatiana Kovacikova; Martin Klimo (Communications - Scientific letters of the University of Zilina, 2002)
Communication networks play an important infrastructural role in the crisis management. To fulfill this role, they have to be robust enough. The robustness is an aspect, which will have to be taken into account also in NGNs (Next Generation Networks). The paper introduces a reference model of the architecture and protocols for robust NGNs. Based on characteristics and requirements for the control architecture, it shows how the control layer can be decomposed, it identifies the basic network elements and the interfaces and protocols that might be used for their interworking. Based on the characteristics and requirements of transport and connectivity layers architecture, and using the examples of different network types and technologies, the authors try to identify the general functions of the transport and connectivity layers in the network.